Report on The Future of AI Workshop - Horvitz, Eric (2002)
Mankind has witnessed an amazing technological development in the field of Information Technology in the latter half of the 20th century, and during that time, Artificial Intelligence has also grown to be an important and irreplaceable discipline of research and application. Now at the beginning of a new era, evaluating the results of AI research from the past years and providing a sense of direction of where to go for the future should be an effort deeply meaningful to any researcher associated with AI. Especially since AI has begun to attract attention again recently, an important responsibility for us is to investigate the kind of AI technology that will be useful to the society and to propose a guideline that the industry can follow. Forecasting the growth of the new fields of technology such as grid computing and web intelligence should also be an important part of the task in planning out the future. In the light of the above intension, we have planned to organize a workshop meeting to discuss the future of AI research, calling upon the intellectual ability of the foremost researchers in this field from Japan, the United States, Europe, and elsewhere. Specifically, the meeting will address the following issues: What were the important research topics that have been neglected in the past ten years but should be taken up in the near future? What will be the important research topics for the next three, five, and ten years? What technology will be necessary to have successful AI applications on the Internet? (e.g. web intelligence, knowledge discovery, intelligent human interface, content creation and AI, business grid and its application) The Workshop meeting will take place on Dec. 14 – 15, 2002 (Reception on Dec. 13), at IBM Japan’s Amagi Homestead in Izu. Following a keynote speech, there will be a series of panel sessions to discuss topics that directly relate to the two main issues of the Workshop stated above. The meeting itself will not be open to public in order to elicit free and active discussion among the participants, but the report may become public through academic and/or commercial publications. It is with great expectation that we organize the Future of AI Workshop, and we sincerely look forward to the participation of the distinguished AI researchers. October, 2002 FUTURE OF AI Workshop Steering Committee Members Edward A. Feigenbaum, Stanford University Setsuo Ohsuga, Waseda University Hiroshi Motoda, Osaka University Koji Sasaki, AdIn Research, Inc.